Studi Komparatif Efektivitas Instagram dan Tiktok terhadap Keterbukaan Diri Mahasiswa Universitas Pancasakti Tegal - Dwi Rizqi Mulyani; Ike Desi Florina; Diryo Suparto (Pusat Riset dan Inovasi Nasional, 2022)
The objective of this study is to determine the extent to which Instagram and TikTok affect the level of self-disclosure among Communication Science students at UPS Tegal. In this manner, the objective is to determine whether Instagram and TikTok are related. Following this, quantitative research was conducted utilizing techniques of purposive sampling. The Slovin formula is applied to 61 UPS Tegal Communication Science students using this method. In this study, Instagram and TikTok serve as the independent and dependent variables, respectively, with regard to self-disclosure. As a data collection instrument, Google Forms is utilized to administer the survey. Validity and reliability assessments are conducted in order to evaluate the instrument. In order to analyze the data, descriptive statistics, pre-requisite tests, and hypothesis testing were implemented. Self-disclosure is positively correlated with Instagram and TikTok, as indicated by the findings of the research data analysis (r = -0.451, greater than 0.176). In conclusion, as the functionality of Instagram and TikTok improves, so does the degree of candor among students.